(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The trophic activity of Acletoxenus formosus, a dipteron with predacious larvae, is reported for the first time to control Trialeurodes vaporariorum populations infesting ornamental Hibiscus outdoor in the Italian western Riviera.